Educação em Economia Solidária: a V Feira Paraibana de Ecosol - Leite, Maria de Lourdes Souza (2011)
Our goal in this study is to analyze the educational dimension in the construction and realization of V Fair Paraibana Solidarity Economy in Paraiba, seeking to identify the elements of the solidarity economy in the process and what is its connection with popular education, the prospect of building a new form of economic organization supportive, aimed at generating employment and income, through practices of solidarity organized by subjects entrepreneurs with the support of Sponsoring Organizations of the Movement in the State and Federal Government. For this, we refer back to 2006, during which the movement of Ecosol Paraiba was awarded by the National Fair Ecosol. As also happened to take up the challenge of inserting an educational space at these events. The central assumption that guided our work in that search was that the educational activities undertaken by institutions that promote the Movement of Paraiba Ecosol have contributed to the subjects see themselves as subjects of law and his actions in organizing resistance capitalist economy. The methodology that we elected to guide our research was the qualitative approach through the techniques of semi-structured interviews, documentary research, photographic documentation, participation in seminars, lectures and activities of the organization and the Fair and literature review. Despite the difficulties, educational activities, present this experience in ways explicitly or implicitly, are focused on the emancipation of the subject in view of (re) places them in their rightful place.